2010
DOI: 10.1007/s12550-010-0063-6
|View full text |Cite
|
Sign up to set email alerts
|

Repair of DNA damage induced by the mycotoxin alternariol involves tyrosyl-DNA phosphodiesterase 1

Abstract: Alternariol (AOH) was reported recently to act as a topoisomerase poison. To underline the relevance of topoisomerase targeting for the genotoxic properties of AOH, we addressed the question whether human tyrosyl-DNA phosphodiesterase 1 (TDP1), an enzyme vital to the repair of covalent DNA-topoisomerase adducts, affects AOH-mediated genotoxicity. The relevance of TDP1 activity on AOH-induced genotoxicity was investigated by the comet assay in human cells overexpressing GFP chimera of TDP1 or the inactive mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
0
16
0
1
Order By: Relevance
“…Cell proliferation studies on Ishikawa and Chinese hamster V79 cells by flow cytometry and microscopy indicated that AOH inhibited cell proliferation by interfering with the cell cycle . Genotoxic effects of AOH have also been reported in these cell lines and in human colon carcinoma cells (Fehr et al, 2010). Reduced cell proliferation has also been associated with DNA damaging effects of AOH (Solhaug et al, 2012).…”
Section: Contents Lists Available At Sciverse Sciencedirectmentioning
confidence: 90%
See 1 more Smart Citation
“…Cell proliferation studies on Ishikawa and Chinese hamster V79 cells by flow cytometry and microscopy indicated that AOH inhibited cell proliferation by interfering with the cell cycle . Genotoxic effects of AOH have also been reported in these cell lines and in human colon carcinoma cells (Fehr et al, 2010). Reduced cell proliferation has also been associated with DNA damaging effects of AOH (Solhaug et al, 2012).…”
Section: Contents Lists Available At Sciverse Sciencedirectmentioning
confidence: 90%
“…AOH is a potent genotoxic, mutagenic, carcinogenic and oestrogenic compound (Brugger et al, 2006;Fehr et al, 2010;Lehmann et al, 2006;Liu et al, 1992). Some mycotoxins cause cytotoxicity to exposed cells whereas others increase cellular proliferation (Frizzell et al, 2011;Ndossi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…As expected by a topoisomerase inhibitor the human tyrosyl-DNA phosphodiesterase I (TDP1), a key enzyme in the repair of covalent DNA-topoisomerase adducts, affects AOH-induced genotoxicity. Human carcinoma cells overexpressing this enzyme presented significantly less DNA breakage than cells expressing a mutant inactive form of TDP1 while damage was increased in TDP1-suppressed cells (Fehr et al, 2010).…”
Section: Mechanism Of Genotoxicitymentioning
confidence: 94%
“…being a topoisomerase poison). Here, also the IIα isoform was preferentially targeted . The collision of the stabilized DNA complex with the DNA replication forks or transcriptional machinery may lead to DSB, thus providing a plausible mechanism for the clastogenic effects of AOH.…”
Section: Aoh‐induced Effects and Consequence – Suggested Mechanistic mentioning
confidence: 99%